Comparative influence of salinity and temperature on cassava flour product by Lactobacillus plantarum and Lactobacillus acidophilus during single culture fermentation - ANDRI FREDIANSYAH; MUHAMAD KURNIADI (Smujo International, 2016)
Abstract. Frediansyah A, Kurniadi M. 2016. Comparative influence of salinity and temperature on cassava flour product by Lactobacillus plantarum and Lactobacillus acidophilus during single culture fermentation. Nusantara Bioscience 8: 207-214. Lactobacillus plantarum (FNCC 0027) and Lactobacillus acidophilus (FNCC 0051) were used as a single culture in cassava fermentation. The effect of salinity (0.5, 1, 2 and 3% (v/v)) and temperatures (4, 25, 30 and 40oC) were investigated on the survival of these lactobacilli. In addition, fiber and moisture content were used to study the characteristic of cassava flour as a final product. About 6.98 cfu/g of L. plantarum and 7.02 cfu/g of L acidophilus were used as a single starter (t = 0 h) for cassava fermentation. After 15 h, the survival rate of both lactobacilli with the salinity of 0.5% and incubation at 40oC were found to be at the highest compared with others. The temperature of incubation was showed in a degree-dependent manner in both reductions of pH to the substrate and fiber contents of flour product. However, it increased the survival of both L. plantarum and L. acidophilus in a degree of temperature-dependent manner. Both salinity and temperature did not give significant effect to further changing of moisture content. The fermentation of cassava could improve proximate composition, cyanide content and physical properties of cassava flour product.